The Effect of Couple Support and Mental Attitude on the Economic Recovery of Salted Fish Traders at Lamekongga Kolaka Market Post COVID-19 PPKM - Neks Triani; Muhammad Fath Azzajjad; Dewi Satria Ahmar (PT Mattawang Mediatama Solution, 2022)
Currently, there are many raw food products circulating in traditional markets, one of which is salted fish. The Covid-19 pandemic has changed economic life, including salted fish traders at the Lamekongga market, Kolaka Regency. The revival of the salted fish business is considered very important because this source of livelihood experienced a decline in income during the COVID-19 outbreak that entered Kolaka Regency. The purpose of this study was to measure the effect of partner support (X1) and mental attitude (X2) on the economic recovery (Y) of salted fish traders in Lamekongga traditional market. This research is an ex-port facto research which is causal associative. The subjects of this study were 19 sellers of salted fish in the Lamekongga traditional market. Data was collected by distributing questionnaires and documentation. Data were analyzed using simple regression and multiple regression. The implication of the research is to describe the recovery economy after the peak of COVID-19. The results of the inferential analysis of the influence of partner support (X1) and mental attitude (X2) on economic recovery (Y), obtained information on the value of sig.2-tailed is 0.000 < 0.05, the test results are statistically significant, thus there is an effect of partner support ( X1) and mental attitude (X2) towards economic recovery (Y).